Thermodynamic properties of ferrofluid: preparation, stability and statistical mechanics - Ahmad Najmi Naqiuddin Che Rosli; Muhamad Alias Md. Jedi; Wan Mohd Faizal Wan Mahmood; Mostafa S. Shadlooc (Penerbit Universiti Kebangsaan Malaysia, 2024)
Ferrofluids are known as magnetic liquids that are colloidal suspensions of ultrafine, single domain magnetic particles in either aqueous or non-aqueous liquids. For such fluids, the problem arises in calculating thermal conductivity, viscosity, and thermodynamic properties on nanoparticles and ferrofluids. Thus, the main objective is to determine thermal conductivity and viscosity for ferro-nanoparticles and ferrofluids. For this study, the ZnO and Fe3O4 are checked for mechanical properties such as SEM, TEM and XRD. Then, being suspended into the diesel engine oil SAE-50 as base fluid and surfactant, Triton-100, in preparation of two-step method. Ferrofluids are prepared for 0.1%, 0.4% & 0.7% w/v and stability of nanofluids are being observed for 5 days. From the results obtained experimentally, the nanoparticles were found to be in good stability as no coagulate occur. This is because the EDLRF acts as the opposite to Van der Waals attractive force which separates the particles from each other. Finally, the thermal conductivity and viscosity for ferro-nanoparticles and ferrofluids were successfully obtained and demonstrated. Statistical mechanics are then discussed to calculate the properties of ferrofluids. The analytical results from statistical mechanics are potentially be used to compare with the experiment data.